PERSON AND PERSONALİTY IN ORGANİZATİONS : THE IMPORTANCE OF WORK AND PERSONALİTY FİT (Third Sector Social Economic Review, 2011)
Personality, defined as the individual’s specific consistent patterns of behaviour. In other saying, personality is the sum of all the behaviours of individuals in their life they prove and characteristics they have. Briefly personality refers to the lifestyle of the individual. this definitions and other definition in the literature emphasized common point is the importance of individual differences. Today, an accepted approach to personelity is shaped changing environmental conditions, social experiences and inherited features by the interaction.Personality caracteristics and behaviours acquired at working life forms part of personality. Reexisting rules/regulations and values has an effect on worker. The organizations take measures to get positive reactions as a result of these effects, for the improvement and of both employee motivation and job satisfaction. Each employee has different characteristics so their responces to these measures is differs.The organizations questioning whether the work is eligible for their employees personality characteristics, if not intraorganizational career change or educational programs on this topic could be organized to raise awernase of employees. And it is clear that this awernase is benaficial for both the employee and the organization. Applications about personality, based on individual differences for the benefit of the business climate is seen as an increase in recent years.
Keywords: Personality; personality fit; personality types